Measuring the Effectiveness of Control Mechanisms in Regional Human Rights Systems – from Conception to Execution - Jarosław Kowalski (Przegląd Prawno-Ekonomiczny)
The lowest level of protection is ensured under the domestic law of individual countries. The aim of the article is to develop a methodology for measuring the effectiveness of control mechanisms functioning within regional human rights protection systems and to access this effectiveness with the use of the proposed solution. The control mechanism can be defined as a set of procedural and institutional norms ensuring the implementation of human rights and freedoms specified in a specific legal system. The effectiveness of control mechanisms in four regional systems was assessed in order to examine the existing level of human rights protection in Europe, America, Africa and the Arab countries. Based on the analysis of the selected criteria, it seems that the most effective system of regional protection of human rights remains the European system operating within the framework of the Council of Europe. This article might be a basis for further research aimed at determining the optimal level of such protection. By optimal level of protection, the author means the highest level that can be obtained today.